2002
DOI: 10.1063/1.1498872
|View full text |Cite
|
Sign up to set email alerts
|

Boron penetration studies from p+ polycrystalline Si through HfSixOy

Abstract: We present detailed B penetration studies from B-doped polysilicon through alternate gate dielectric candidate HfSixOy films. No detectible B penetration is observed for annealing times as long as 20 s after 950 °C. Considerable B incorporation into the Si substrate is observed for annealing temperatures higher than 950 °C. By modeling the B depth profiles, we calculated the B diffusivities through HfSixOy to be higher than the corresponding diffusivities for SiO2. B diffusion through grain boundaries after Hf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 15 publications
1
26
1
Order By: Relevance
“…Silicates with low concentrations of the Hf cation ($2-8%) are shown to retain their amorphous structure and demonstrate interface stability with silicon to temperatures of 1050°C [149]. Hafnium silicate dielectrics with a $0.52 Si/Hf ratio are shown to resist boron penetration up to 950°C [182]. It is believed that after the phase separation and crystallization occurs, grain boundary diffusion is responsible for the onset of enhanced B diffusivity compared to pure SiO 2 dielectrics.…”
Section: Hf-based Oxides Gate Dielectricsmentioning
confidence: 97%
“…Silicates with low concentrations of the Hf cation ($2-8%) are shown to retain their amorphous structure and demonstrate interface stability with silicon to temperatures of 1050°C [149]. Hafnium silicate dielectrics with a $0.52 Si/Hf ratio are shown to resist boron penetration up to 950°C [182]. It is believed that after the phase separation and crystallization occurs, grain boundary diffusion is responsible for the onset of enhanced B diffusivity compared to pure SiO 2 dielectrics.…”
Section: Hf-based Oxides Gate Dielectricsmentioning
confidence: 97%
“…However, considering that the process temperature for the activation of impurities in the source/drain of MOSFET is as high as 1,000°C, the capability of Hf silicate as a diffusion barrier is insufficient. Moreover, it is reported that phosphorous and arsenic diffused through the HfSiO with the same Hf concentration during 1,000°C rapid thermal annealing (RTA) [80]. Such impurity diffusion is ascribed to the enhanced diffusion at the grain boundaries formed in the resultant 'phase separation phenomena' in HfSiO at high temperatures [79,80] as described below.…”
Section: Hafnium-nitrogen-based Gate Dielectricsmentioning
confidence: 95%
“…SiO 2 incorporation is also effective for suppressing the impurity penetration phenomena, which are problematic when poly-Si gate electrode is used. Boron diffusion through the HfSiO film with the Hf/Hf+Si ratio of 0.52 (atomic concentration of Hf is about 10-12 %) is suppressed up to 950°C [79]. However, considering that the process temperature for the activation of impurities in the source/drain of MOSFET is as high as 1,000°C, the capability of Hf silicate as a diffusion barrier is insufficient.…”
Section: Hafnium-nitrogen-based Gate Dielectricsmentioning
confidence: 98%
“…However, dopant penetration from the poly-Si through the crystallized high-k gate dielectrics during high-temperature annealing results in unstable electrical characteristics. Quevedo-Lopez et al 2 recently reported that phosphorus ͑P͒ penetrates through crystalline HfSi x O y into the Si substrate after rapid thermal annealing ͑RTA͒ at 1050°C whereas P penetration was largely reduced when amorphous HfSi x O y N z films were used.…”
Section: Phosphorus Ion Implantation Andmentioning
confidence: 97%